Report of the Committee for Evaluation and on Public Participation Uttar Pradesh 1959 - Government of Uttar Pradesh (Government of Uttar Pradesh, 1959)
The 1959 evaluation report of the Community Development Programme in Uttar Pradesh, prepared by the Committee for Evaluation and Public Participation under the leadership of Govind Sahai, presents a comprehensive assessment of the functioning of the National Extension Service and Community Development Blocks with a focus on strengthening rural transformation through effective public participation and administrative reform. Situating the programme within the broader historical evolution of rural reconstruction in India, influenced by thinkers such as Mahatma Gandhi and Rabindranath Tagore, the report identifies both achievements and structural shortcomings in implementation. It emphasizes the pivotal role of the Village Level Worker and Block Development Officer while recommending specialization over multipurpose roles, administrative decentralization, integration of development departments, equitable pay structures, and improved recruitment practices favoring rural-oriented candidates. The committee underscores the necessity of empowering Panchayati Raj institutions, particularly Gaon Panchayats and Nyaya Panchayats, through grant-in-aid mechanisms, advance funding, and simplified procedures to enhance local initiative and resolve land-related disputes efficiently. Strong emphasis is placed on training, continuous research, and reorientation of objectives to align development efforts with community aspirations. Sectoral evaluations reveal progress in primary education expansion, rising female enrollment, infrastructure creation, sanitation, drinking water supply, and public health facilities, yet highlight persistent concerns regarding educational quality, health awareness, economic uplift of Scheduled Castes and backward classes, and sustainability of community participation. The report ultimately advocates structural restructuring, strengthened coordination between governmental and non-governmental bodies, enhanced leadership development, and transparent administrative processes to foster genuine people’s participation and self-governance. It concludes that meaningful rural transformation depends upon decentralization, administrative coherence, and empowered local institutions working in partnership with an informed and actively engaged rural populace.
N.E.S. & Community Projects
N.E.S. & Community Projects
Keywords: Community Development Programme; National Extension Service; Public Participation; Panchayati Raj Institutions; Administrative Decentralization; Village Level Worker; Block Development Officer; Rural Education Expansion; Public Health Initiatives; Local Leadership Development; Grant-in-Aid System; Socio-Economic Transformation